Multiplexed LC‐MS / MS quantification of salivary RNA modifications in periodontitis - Vignon, Margaux; Bastide, Amandine; Attina, Aurore; David, Alexandre; Bousquet, Philippe; Orti, Valérie; Vialaret, Jérôme; Lehmann, Sylvain; Periere, Dominique DevilleDe; Hirtz, Christophe (Journal of periodontal research, 2023)
To analyse the salivary epitranscriptomic profiles as periodontitis biomarkers using multiplexed mass spectrometry (MS). The field of epitranscriptomics, which relates to RNA chemical modifications, opens new perspectives in the discovery of diagnostic biomarkers, especially in periodontitis. Recently, the modified ribonucleoside N6-methyladenosine (m6A) was revealed as a crucial player in the etiopathogenesis of periodontitis. However, no epitranscriptomic biomarker has been identified in saliva to date. Twenty-four saliva samples were collected from periodontitis patients (n = 16) and from control subjects (n = 8). Periodontitis patients were stratified according to stage and grade. Salivary nucleosides were directly extracted and, in parallel, salivary RNA was digested into its constituent nucleosides. Nucleoside samples were then quantified by multiplexed MS. Twenty-seven free nucleosides were detected and an overlapping set of 12 nucleotides were detected in digested RNA. Among the free nucleosides, cytidine and three other modified nucleosides (inosine, queuosine and m6Am) were significantly altered in periodontitis patients. In digested RNA, only uridine was significantly higher in periodontitis patients. Importantly there was no correlation between free salivary nucleoside levels and the levels of those same nucleotides in digested salivary RNA, except for cytidine, m5C and uridine. This statement implies that the two detection methods are complementary. The high specificity and sensitivity of MS allowed the detection and quantification of multiple nucleosides from RNA and free nucleosides in saliva. Some ribonucleosides appear to be promising biomarkers of periodontitis. Our analytic pipeline opens new perspectives for diagnostic periodontitis biomarkers.